Recreational drug poisoning with gamma-butyrolactone and 1,4-butanediol in Taiwan - Feng-Chen Chen; Yan-Chiao Mao; Jou-Fang Deng; Cheng-Hsuan Ho (Journal of Medical Sciences, 2023)
Restriction of gamma-hydroxybutyrate (GHB) in 1990 resulted in a shift toward the use of gamma-butyrolactone (GBL) or 1,4-butanediol (1,4-BD), which remain unregulated in most countries, including Taiwan. Self-reported GBL and 1,4-BD use are less common than GHB use, and the prevalence of GBL or 1,4-BD abuse may be underestimated. The first patient, a 45-year-old male, used GBL to enhance his sexual activity. He developed respiratory system and central nervous system (CNS) suppression; he was intubated and admitted to the intensive care unit. His urine GHB concentration was 289.5 mg/L. The second patient was a 24-year-old male who used 1,4-BD in conjunction with mixed new psychoactive substances to enhance his sexual activity. He also developed CNS suppression, and his urine GHB concentration was 1192.4 mg/L. By reporting these cases, we highlight the recreational use of GHB precursors, such as GBL and 1,4-BD, which is relatively unfamiliar to clinicians. Patients may present with CNS and respiratory depression after the voluntary recreational use of these drugs.